Association between heat stress risks for Muslim pilgrims among Elderly pilgrims attending primary health care Center, Makah Al-Mokarrama, Saudi Arabia 2023 - Alotaibi, Nayef Awn Nayaf; Alfawzan, Musaad Ibrahim Bin Abdullah; alfawzan, Alwaleed Naif; Alfouzan, Yousef Mohammed A; Alfozan, Abdullah Ibrahim A; alsahli, Abdulmajeed Nasser Abdullah; Mabuj, Ghena Ibrahim Ali; Sarah Abdulaziz alhoyme; Nowayer saad sayed; Tahani Ibrahim Ali Mabuj; Seham brahim alhoymel (Migration Letters, 2023)
Background The pilgrimages of Muslims to Makah (Hajj and Umrah) is one of the largest religious gatherings in the world which draws millions of people from around 180 countries each year. Heat stress during summer has led to health impacts including morbidity and mortality in the past, which is likely to worsen due to global warming. Here we investigate the impacts of increasing heat stress during the peak summer months over Makah at present levels of warming as well as . We find a substantial increase in the exceedance probabilities of dangerous thresholds (wet-bulb temperature >24.6 ◦C) in 1.5 ◦C and 2 ◦C warmer worlds over the summer months. For the 3 hottest months, August, September and October, even thresholds of extremely dangerous (wet-bulb temperature >29.1 ◦C) health risks may be surpassed. September shows the highest increase in the exceedance probability of extremely dangerous threshold which is increased to 4 and 13 times in 1.5 ◦C and 2 ◦C warmer worlds respectively. Based on the indicators of hazard, exposure and vulnerability, we carried out probabilistic risk analysis of life-threatening heat stroke over Makah. A ten time increase in the heat stroke risk at higher wet-bulb temperatures for each month is projected in 2 ◦C warmer world. Aim of the study: To assessment Association between heat stress risks for Muslim pilgrims among Elderly pilgrims attending primary health care Center, Makah Al-Mokarrama, Saudi Arabia 2023 Methods: Across sectional descriptive study conducted among pilgrims who attending at primary Health care Center Makah city during July, 2023 to October 2023 Hajj 2023, Our total Sample size of pilgrims participants were (700) Results[1]: show that the highest proportion of participants age 51-60 years (24.0%) regarding the sex the majority of participant male were (61.0%), the marital status the majority of participant married were (61.0%) pregnancy status the majority of participant Non- pregnant Female were (64.84%), the have ​chronic diseases the majority of participant answer Yes (68.0%) Conclusion: Both hazards of heat exposure, heat Illnesses, communicable and non-communicable health issues are the most common health problems encountered by pilgrims during Hajj, especially elderly and pregnant pilgrims, need necessity of new research’s to find solutions to pilgrims’ health problems during Hajj.